Design of Halal Traceability System Model for Rectangular Veil Products at PT. X and PT. Y - Wardiani, Gina Rahayu (Universitas Insan Cendekia Mandiri, 2024)
Based on the mandate of Law Number 33 of 2014 concerning guarantees for halal products, that all products circulating in the market including goods used or utilized by the public must be halal, one of which is textile and clothing products. Currently, not many textile and clothing products are halal-certified. Whereas textile and clothing products have great potential to develop their business in supporting the strengthening of the value chain in the halal industry. Halal traceability is one of the halal requirements that must be met in the manufacture of halal products, this is stated in the Halal Product Guarantee (JPH) HAS 23000. Halal traceability is also an important factor in maintaining halal integrity. There are various methods used in developing a halal traceability system. One of them is the IDEF0 method. The IDEF0 method can be used in determining plans to capture traceability information needed by internals. In addition, IDEF0's simple notation construction consisting of input, control, output, mechanism (ICOM) becomes the main strength as a communication tool that is easily understood by everyone. Therefore, this study develops a model of a halal traceability system based on critical activities that can change the halal status of a product with the IDEF0 method in the Small Medium Enterprises (SMEs) of Muslim women's clothing. Based on the results of the study, there are six critical activities that affect the halal status of products during the production process, namely, material purchasing activities, material receiving and storage activities, supply to production activities, production activities, finished product storage activities, and outgoing transportation activities.